Delineation of Steroid-Degrading Microorganisms through Comparative Genomic Analysis - Lee H. Bergstrand (American Society for Microbiology, 2016)
ABSTRACT Steroids are ubiquitous in natural environments and are a significant growth substrate for microorganisms. Microbial steroid metabolism is also important for some pathogens and for biotechnical applications. This study delineated the distribution of aerobic steroid catabolism pathways among over 8,000 microorganisms whose genomes are available in the NCBI RefSeq database. Combined analysis of bacterial, archaeal, and fungal genomes with both hidden Markov models and reciprocal BLAST identified 265 putative steroid degraders within only Actinobacteria and Proteobacteria, which mainly originated from soil, eukaryotic host, and aquatic environments. These bacteria include members of 17 genera not previously known to contain steroid degraders. A pathway for cholesterol degradation was conserved in many actinobacterial genera, particularly in members of the Corynebacterineae, and a pathway for cholate degradation was conserved in members of the genus Rhodococcus. A pathway for testosterone and, sometimes, cholate degradation had a patchy distribution among Proteobacteria. The steroid degradation genes tended to occur within large gene clusters. Growth experiments confirmed bioinformatic predictions of steroid metabolism capacity in nine bacterial strains. The results indicate there was a single ancestral 9,10-seco-steroid degradation pathway. Gene duplication, likely in a progenitor of Rhodococcus, later gave rise to a cholate degradation pathway. Proteobacteria and additional Actinobacteria subsequently obtained a cholate degradation pathway via horizontal gene transfer, in some cases facilitated by plasmids. Catabolism of steroids appears to be an important component of the ecological niches of broad groups of Actinobacteria and individual species of Proteobacteria. IMPORTANCE Steroids are ubiquitous growth substrates for environmental and pathogenic bacteria, and bacterial steroid metabolism has important pharmaceutical and health applications. To date, the genetics and biochemistry of microbial steroid degradation have mainly been studied in a few model bacteria, and the diversity of this metabolism remains largely unexplored. Here, we provide a bioinformatically derived perspective of the taxonomic distribution of aerobic microbial steroid catabolism pathways. We identified several novel steroid-degrading bacterial groups, including ones from marine environments. In several cases, we confirmed bioinformatic predictions of metabolism in cultures. We found that cholesterol and cholate catabolism pathways are highly conserved among certain actinobacterial taxa. We found evidence for horizontal transfer of a pathway to several proteobacterial genera, conferring testosterone and, sometimes, cholate catabolism. The results of this study greatly expand our ecological and evolutionary understanding of microbial steroid metabolism and provide a basis for better exploiting this metabolism for biotechnology.